Postponements of cases : effects and implications / Mohd Shahar Ismail - Ismail, Mohd Shahar (Faculty of Law, 1987)
Postponement is derived from the word postpone. The Penguin English Dictionary define 'postpone' as 'put off till later time or defer‘. Thus to postpone a case means to defer the case to a later date or time. Egetgptenments of cases can justiflably be said to be one of the real problems facing the hearing pf noth criminal and civil cases in Subordinate Courts. Though these problems are easily identifiable theoritically in real practice. it would be impossible to eliminate. However if may be possible that this problem-could be minimisedwhat could be done is perhaps to bring then within administra— tive (and possibly legal) control. It needs a good and careful planning which inevitably requires harmonious co—ordinations by parties concerned with the administration of justice. The aim of this paper is to discuss the'instances of post ponements of both criminal and civil cases, their effects and ways to eliminate or minimise them.